2016
DOI: 10.18203/2394-6040.ijcmph20161594
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of depression and its associated factors among medical students of a private medical college in south India

Abstract: Medical training is full of stress and this has been a topic of concern for nearly half a century. 1 Various stressors in the life of a medical student include homesickness, heavy workload, sleep deprivation, difficult patients, financial concerns, information overload and career planning. 2 These stressors often have a negative impact on the students' academic performance, physical health, and psychological well-being, making them more susceptible to depression. 3,4 This is harmful not only for the students b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
13
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 4 publications
4
13
1
Order By: Relevance
“…It also differed from the study done by Aniebue, et al also in the University of Nigeria, Enugu Campus which put the prevalence of depression at 23.3% [48]. It also differs from indings in other parts of the world which put the prevalence of depression among medical students between 21% -39% [25][26][27]50,[71][72][73][74][75][76].…”
Section: Discussionmentioning
confidence: 70%
“…It also differed from the study done by Aniebue, et al also in the University of Nigeria, Enugu Campus which put the prevalence of depression at 23.3% [48]. It also differs from indings in other parts of the world which put the prevalence of depression among medical students between 21% -39% [25][26][27]50,[71][72][73][74][75][76].…”
Section: Discussionmentioning
confidence: 70%
“…Similar figures (28%) were also obtained in another meta-analysis of 77 studies (12,24). However, much higher rates, as high as 58% (5) have been reported from studies conducted in India. Other studies have also shown high prevalence, 51.3% from Odisha (22) and 45.4% from Andhra Pradesh (24).…”
Section: Discussionmentioning
confidence: 88%
“…The transition from school education to professional college is a major turning point for a young adult, causing mal-adjustments. Depression is commonly reported by university students (5,6) due to change in environment, academic demands, developing new relations and more financial freedom (7). If that professional course happens to be medical education, the transition is even more drastic (8).…”
Section: Introductionmentioning
confidence: 99%
“…[4] Also, the need to support the students during the period of training has been suggested through the provision of counselling services so as to detect and manage cases of depression as early as possible. [12] The highest proportion of the respondents who were depressed were in the third year of their study, followed by rst year students, while the least proportion were in the nal year. The third year remain the most critical in the life of the medical student in Nigeria as it is the year of the rst professional examination for the students.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it has been postulated that mechanisms to facilitate early detection including prevalence studies, counselling services and treatment of depression among medical students should be provided in medical schools. [12] Equally important is the need to quantify the burden of depression and factors associated with it among medical students so as to enhance their counselling and efforts toward rehabilitation. [13,14] Su ce it to say that medical students of today are the physicians of tomorrow hence the need to pay attention to issues related to their mental health.…”
Section: Introductionmentioning
confidence: 99%